A complicated pregnancy in homozygous familial hypercholesterolaemia treated with lipoprotein apheresis: A case report. (December 2019) - Perrone, Seila; Perrone, Giuseppina; Brunelli, Roberto; Di Giacomo, Serafina; Galoppi, Paola; Flammini, Guendalina; Morozzi, Claudia; Stefanutti, Claudia
Abstract: Background and aims: During pregnancy total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) levels increase significantly and lipoprotein apheresis (LA) is considered the most effective therapy in homozygous familial hypercholesterolaemia (HoFH) for modulating lipid and lipoprotein levels and reducing maternal and foetal complications. Clinical case: A primigravida 28 years old Caucasian female patient, previously diagnosed as to be HoFH, was admitted at our outpatient service at the beginning of pregnancy. Methods: The patient was continuously submitted to LA every two weeks without foetal complication. During pregnancy two methods have been utilised: selective apheresis, and later plasma exchange. At 33 weeks gestational age the patient developed progressively hypertension, associated to LDL-C levels increase. Weekly LA was favoured. Results: At 34 weeks +5 days patient suddenly experienced acute chest pain and abnormal electrocardiogram heart tracing and cardiac enzymes increase. An emergency caesarean section was performed without complications and the foetus was healthy. The patient was immediately transferred to Coronary Intensive Care Unit, where she was diagnosed non-ST elevation myocardial infarction (NSTEMI). Notwithstanding the patient improved in few days and was quickly discharged in fair clinical condition. Conclusions: LA is a safe and effective tool in HoFH subjects even in pregnancy. Evidence based guidelines for the management of these patients during pregnancy are still lacking.